2021
DOI: 10.1016/j.jpsychires.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Depression risk factors and affect dynamics: An experience sampling study

Abstract: Affect dynamics reflect individual differences in how emotional information is processed, and may provide insights into how depressive episodes develop. To extend prior studies that examined affect dynamics in currently depressed individuals, the present study tested in 68 nondepressed young adults whether three well-established risk factors for major depressive disorder (MDD) -(a) past episodes of MDD, (b) family history of MDD, and (c) reduced neurophysiological responses to reward -predicted mean levels, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 65 publications
2
16
1
Order By: Relevance
“…[62][63][64] Moreover, previous history and family history can also contribute to the occurrence of future MDD episodes in individuals. 65 Few previous findings have shown consistency with our results. A study conducted by Chen et al on 25 MDD patients and 20 HCs, observed that MDD patients exhibited elevated serum IL-2 levels than HCs establishing a considerable positive correlation between serum cortisol and IL-2, as well as ACTH and IL-2.…”
Section: Discussionsupporting
confidence: 92%
“…[62][63][64] Moreover, previous history and family history can also contribute to the occurrence of future MDD episodes in individuals. 65 Few previous findings have shown consistency with our results. A study conducted by Chen et al on 25 MDD patients and 20 HCs, observed that MDD patients exhibited elevated serum IL-2 levels than HCs establishing a considerable positive correlation between serum cortisol and IL-2, as well as ACTH and IL-2.…”
Section: Discussionsupporting
confidence: 92%
“…These bidirectional relationships may be important for targeted intervention since targeting 1 symptom dimension may prevent increases in others. Future research should use ecological momentary assessments 43 to further investigate the dynamic nature of these depression symptoms and examine how somatic symptoms and anhedonia are impacted by different treatments in different stroke groups.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy controls reported no lifetime mental disorders. For both groups, additional exclusion criteria included a history of a current major depressive episode and substance use disorders (see Funkhouser et al, 2021). One hundred and four participants from the parent study were recontacted.…”
Section: Methodsmentioning
confidence: 99%